Sifat organoleptik dan kadar protein pada rolade ikan lele dumbo (Clarias gariepinus) dengan penambahan tepung kacang kedelai - Janet Annisa Sanditya; Linda Riski Sefrina; Milliyantri Elvandari (Poltekkes Kemenkes Aceh, 2023)
Background: Rolade is a processed product made from a mixture of finely ground meat with flour or strach. Generally, rolade used beef as the main ingredient. This study used african catfish as the main ingridient and the addition of soybean flour to increase the nutritional contents of rolade as specially protein content.Objectives: This study amied was to analyzes the effect soybean flour subsitution on the nutritional contents (moisture, ash, fat, protein, carbohydrate, and iron) and to assess changed in the organolpetic propoerties if rolade after vacuum packaging.Methods: This design in this study was used a experimental dsign with a completely randomized design. There are 3 treatment levels (tapioca flour : soybean flour), namely 100:0 (0%), 80:20 (20%), 70:30 (30%). Rolade organoleptic testing was carried out in a Food Processing Labory at Karawang Singaperbangsa University and nutritional analysis was carried out in a Food Technology Labory at Pasundan University. Statistical analysis was used the Kruskal Wallis Test and the Mann Whitney follow-up test.Results: The addition of soybean flour in general didn’t have a significant to the hedonic yield and hedonic quality on all rolade assessment attributes (p>0,05). Vacuum packaging and cold temperature storage didn’t have a significant difference to all rolade assessment atributes (p>0,05). The addition of soybean flour increase the protein content of the rolade.Conclusion: The addition of soybean flour has an effect on the organoleptic of catfish rolade. Vacuum packaging and cold storage can maintained rolade for 14 days. Rolade protein content added to soybean flour has increased.